Nilai-Nilai Pendidikan Dalam Upacara Wetonan Pada Masyarakat Hindu Etnis Jawa - Duwi Oktaviana (Jayapangus Press, 2020)
The theme of this study is wetonan that discusses the values of tattva, ethics, and ceremonies. The Java society still implement it especially for children, while for adults it is rarely implemented. The research carried out for the purpose of knowing the values of Hindu education contained in a wetonan ceremony. This studi uses qualitative methods that produce descriptive data. The result of this study that in the ceremony of the wetonan contain of Hindu educations values, include: Tattva, ethics, and ceremonies that can be known from the aspect of the offerings, prayers, and spells are used.